Marine ecosystem connectivity mediated by migrant–resident interactions and the concomitant cross‐system flux of lipids. Issue 12 (19th May 2016) - van Deurs, Mikael; Persson, Anders; Lindegren, Martin; Jacobsen, Charlotte; Neuenfeldt, Stefan; Jørgensen, Christian; Nilsson, P. Anders
Abstract: Accumulating research argues that migrants influence the functioning and productivity of local habitats and ecosystems along migration routes and potentially drive cross‐system energy fluxes of considerable magnitude, yet empirical documentation of local ecological effects and descriptions of the underlying mechanisms are surprisingly rare. In this study, we discovered migrant–resident interactions and substantial cross‐system lipid transportation in the transition zone between the Baltic Sea and the North Sea where a resident cod population (predators) was found to interact with a herring population (prey) on a seasonal basis. We traced the lipids, using fatty acid trophic markers (FATM), from the herring feeding grounds in the North Sea to the cod livers in the Western Baltic Sea. Time series analysis of population dynamics indicated that population‐level production of cod is positively affected by the herring subsidies. However, the underlying mechanisms were more complicated than anticipated. During the herring season, large cod received most of its dietary lipids from the herring, whereas smaller cod were prevented from accessing the lipid pool due to a mismatch in predator–prey size ratio. Furthermore, while the herring were extremely rich in bulk energy, they were surprisingly poor in a specific functional fatty acid. Hence, our study was the first to illustrate how the magnitude cross‐system fluxes of subsidies in migrant–resident systems are potentially constrained by the size structure of the resident predator population and the nutritional quality of the migrants. Abstract : Accumulating research argues that migrants influence the functioning and productivity of local habitats and ecosystems along migration routes and potentially drive cross‐system energy fluxes of considerable magnitude, yet empirical documentation of local ecological effects and descriptions of the underlying mechanisms are surprisingly rare. In this study, we discovered size‐dependent migrant–resident interactions and cross‐system lipid transportation in the transition zone between the Baltic Sea and the North Sea where a resident cod population (predators) was found to interact with a herring population (prey) on a seasonal basis.